2016
DOI: 10.1016/j.bbadis.2016.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian ataxin-2 modulates translation control at the pre-initiation complex via PI3K/mTOR and is induced by starvation

Abstract: Ataxin-2 is a cytoplasmic protein, product of the ATXN2 gene, whose deficiency leads to obesity, while its gain-of-function leads to neural atrophy. Ataxin-2 affects RNA homeostasis, but its effects are unclear. Here, immunofluorescence analysis suggested that ataxin-2 associates with 48S pre-initiation components at stress granules in neurons and mouse embryonic fibroblast, but is not essential for stress granule formation. Coimmunoprecipitation analysis showed associations of ataxin-2 with initiation factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
77
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 73 publications
5
77
0
Order By: Relevance
“…Ataxin-2 is considered a cytoplasmic protein that is localised at the rough endoplasmic reticulum (rER) [124]. The globular domains (Lsm and LsmAD) are two regions that are highly conserved in proteins thought to be involved the process of RNA metabolism, such as splicing and modification [125,126]. The Lastres-Becker et al study, found that when starved, mouse and human ataxin-2, was able to modulate translational control at the pre-initiation complex via PI3K/mTOR pathways [125].…”
Section: Wild-type and Mutant Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Ataxin-2 is considered a cytoplasmic protein that is localised at the rough endoplasmic reticulum (rER) [124]. The globular domains (Lsm and LsmAD) are two regions that are highly conserved in proteins thought to be involved the process of RNA metabolism, such as splicing and modification [125,126]. The Lastres-Becker et al study, found that when starved, mouse and human ataxin-2, was able to modulate translational control at the pre-initiation complex via PI3K/mTOR pathways [125].…”
Section: Wild-type and Mutant Proteinmentioning
confidence: 99%
“…The globular domains (Lsm and LsmAD) are two regions that are highly conserved in proteins thought to be involved the process of RNA metabolism, such as splicing and modification [125,126]. The Lastres-Becker et al study, found that when starved, mouse and human ataxin-2, was able to modulate translational control at the pre-initiation complex via PI3K/mTOR pathways [125]. This study highlights another possible major function of ataxin-2, its ability to regulate some metabolic activity with a study in C. elegans showing that down regulation of the ataxin-2 homolog leads to fat storage and an increase in growth.…”
Section: Wild-type and Mutant Proteinmentioning
confidence: 99%
“…They confirmed that Pbp1 as the yeast orthologue of Ataxin-2 is being controlled by AMP-kinase phosphorylation signals. Human Ataxin-2 is transcriptionally induced during starvation, and the Ataxin-2 protein relocalizes to stress granules in periods of glucose deprivation or oxidative stress [6, 7]. Downstream effects of Ataxin-2 include the repression of mTOR-dependent phosphorylation signals, but also the enhancement of PINK1-dependent phosphorylation signals [1, 68].…”
mentioning
confidence: 99%
“…Human Ataxin-2 is transcriptionally induced during starvation, and the Ataxin-2 protein relocalizes to stress granules in periods of glucose deprivation or oxidative stress [6, 7]. Downstream effects of Ataxin-2 include the repression of mTOR-dependent phosphorylation signals, but also the enhancement of PINK1-dependent phosphorylation signals [1, 68]. Via Ataxin-2 occurs also a regulation of the cell size, of the availability of lipid and glycogen stores as alternative fuels in times of high bioenergetic demands, and of ribosomal translation during stress periods [6, 8].…”
mentioning
confidence: 99%
See 1 more Smart Citation